Diffusion of Electronic Health Records and electronic communication in Norway - Heimly, V.; Grimsmo, A.; Faxvaag, A. (Applied Clinical Informatics, 2011)
Objective: To assess the diffusion of Electronic Health Record (EHR) systems over time in Norwegian health care.Methods: This study was based on a retrospective cross-sectional questionnaire survey. Questionnaires for three groups of responders were based on two validated questionnaires from prior studies, which were further customized through workshops. The questionnaires were sent to a random sample of 180 municipalities and 150 general practices in all 26 hospitals in Norway.Results: The diffusion curves for EHR systems from 1980 to 2008 were established and analyzed. The most striking finding was the length of time from the availability of the first adequate EHR systems until full coverage was achieved in general practice and in hospitals. Diffusion of EHRs into nursing homes and maternal and child health centers started ten years later, and the diffusion for these centers has also been slow. In general practice the diffusion seems to follow the classical s-curve of diffusion. Costs and the increasing complexity of EHR systems were regarded by respondents as the most important challenges and concerns for the future. Resistance among health personnel was seen only as a small problem.Conclusion: National strategic processes account for the slow diffusion and complexity of EHR systems in the health sector.
Keywords: Electronic health records; primary care; hospitals; general practice; nursing home; diffusion